Larval and Acute Oral Toxicity of Calotropis Procera and Ficus Umbellata, Plants Traditionally Used to Treat Hemorrhoids in Benin - Yomakou, Bato Georges G. René; GLIMMA, Laurent; GLIMMA, Laurent; Assogba, Fidèle; GLIMMA, Bienvenu; AHOTON, Djidénou; AKAKPO, Baï Huguette; AHOTON, Djidénou; AHOUNOU AÏKPE, FIFAMIN JUDITH; YAYI LADEKAN, Eléonore; KPOVIESSI, Salomé; GBENOU, Djimon Joachim (My University, 2023)
n the modern days, investigation of the phytochemical compounds contained in the traditionallyacknowledged medicinal plants have established significant interest in drug research and developmental projects. In addition, phytochemical compounds in plants are compounds delivered by plants having pharmacological or toxicological properties in man and animals. Calotropis procera (Ait.) and Ficus umbellata (Vahl.) are two medicinal plants used in Benin. Their various preparations were used to treat a number of ailments and diseases, including hemorrhoids. Here, before checking their effects on hemorrhoids, toxicity studies were carried out on the decoction of F. umbellata leaves and those of C. procera with and without potash as used in the traditional treatment of hemorrhoids in Benin. Toxicity test results demonstrated tolerance of the leaves to Artemia salina larvae with all their LC50 > 0.10 mg/mL (0.147 for extract of F. umbellata, 0.224 for extract without potash of C. procera and 0.887 for extract with potash of C. procera) and albino rats of the wistar strain in acute oral toxicity at a single dose of 2000 mg/kg body weight. Studies of chronic and sub-chronic toxicity, as well as the anti-inflammatory activity of the extracts, are in prospect
Keywords: medicinal plants; extracts; phytochemistry; toxicity; cytotoxicity